2021
DOI: 10.1111/lam.13474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus subtilis and its metabolites on corn silage quality

Abstract: Cellulolytic micro‐organisms are potent silage inoculants that decrease the fibrous content in silage and increase the fibre digestibility and nutritional value of silage. This study aimed to evaluate the effects of Bacillus subtilis CCMA 0087 and its enzyme β‐glucosidase on the nutritional value and aerobic stability of corn silage after 30 and 60 days of storage. We compared the results among silage without inoculant (SC) and silages inoculated with B. subtilis 8 log10 CFU per kg forage (SB8), 9 log10 CFU pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
1
13
2
Order By: Relevance
“…Members of Bacillus are endospore-forming aerobic or facultatively anaerobic bacteria. Some species of this genus can produce cellulase or other enzymes like α-amylase and feruloyl esterase to degrade plant structural carbohydrates during ensiling ( 52 , 53 ). The Bacillus species also produces lactic acid but is generally less efficient than LAB.…”
Section: Resultsmentioning
confidence: 99%
“…Members of Bacillus are endospore-forming aerobic or facultatively anaerobic bacteria. Some species of this genus can produce cellulase or other enzymes like α-amylase and feruloyl esterase to degrade plant structural carbohydrates during ensiling ( 52 , 53 ). The Bacillus species also produces lactic acid but is generally less efficient than LAB.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the higher AA concentrations in the LB and BS groups at AS0, inhibiting the growth of aerobic microorganisms ( Basso et al, 2012 ). In addition, BS can produce antifungal and antibacterial substances that inhibit the growth of undesirable microorganisms such as yeast ( Bonaldi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that inoculation of B. subtilis in silage can improve silage fermentation ( Guo et al, 2022 ), by producing cellulases, converting water soluble carbohydrates into lactic acid and decreasing pH, thereby inhibiting harmful microbial activity, and has the potential to be a silage inoculant ( Li et al, 2018 ). In addition, researchers have confirmed that B. subtilis can produce antifungal and antibacterial substances, that can inhibit the growth of undesirable microorganisms such as yeast and filamentous fungi, and prevent silage spoilage and mycotoxin production ( Bonaldi et al, 2021 ), which may be applicable to improving aerobic stability. Inoculation with B. subtilis can improve the aerobic stability of silage ( Bumbieris et al, 2017 ; Bai et al, 2020 ), but studies on its role in whole plant corn silage are inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have demonstrated that some metabolites of Bacillus subtilis (BS) can have antibacterial properties, and it can produce lactic acid by reducing pyruvate in anaerobic environment ( Gandra et al, 2017 ; Lanna-Filho et al, 2017 ). In addition, BS and its metabolites can significantly increase the amount of lactic acid bacteria and aerobic stability in corn silages when used as a silage additive ( Bonaldi et al, 2021 ). The natural organic acid gallic acid (GA), also known as 3,4,5-trihydroxybenzoic acid, has three phenolic hydroxyl groups and one carboxyl group ( Badhani et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%